Optimization and coordination of sources – Hydro and diesel generation - Gengathara, S.; Dharmakeerthi, P.G.H.C.H.; Atputharajah, A.; Ekanayake, J.B. (My University, 2005)
Hybrid generations are increasingly employing in power systems due to their advantageous in nature. The intermittent nature of the renewable energy sources makes them not suitable for off grid operation or in large scale grid connected operation. It was found that Sri Lanka is rich with micro hydro potential. It is required to get maximum out of this resource. A micro hydro-diesel hybrid system found to be an ideal solution with the consideration of economical and environmental factors. The proposed system is designed to operate either in islanding mode or in grid-connected mode while fulfilling continuous power demand. A control, with main and supervisory sections, was developed. The main controller in the hydro generator maintains the voltage and frequency with regulatory control while the diesel generator functioning on a droop control. The supervisory controller implemented in the diesel generator to optimize the total generation cost. In addition the supervisory controller coordinates the diesel generator on/off operations with the micro hydro generator. The proposed control system was simulated and the results show excellent performance.